2016
DOI: 10.1007/s10549-016-3759-2
|View full text |Cite
|
Sign up to set email alerts
|

Randomized sham-controlled pilot trial of weekly electro-acupuncture for the prevention of taxane-induced peripheral neuropathy in women with early stage breast cancer

Abstract: PURPOSE To investigate the effect of electro-acupuncture (EA) as a non-pharmacological intervention to prevent or reduce chemotherapy-induced peripheral neuropathy (CIPN) in breast cancer patients undergoing chemotherapy of taxane. METHODS Women with stage I-III breast cancer scheduled to receive taxane therapy were randomized to receive a standardized protocol of 12 true or sham EA (SEA) weekly treatments concurrent with taxane treatment. Subjects completed the Brief Pain Inventory-Short Form (BPI-SF), Func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
144
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(148 citation statements)
references
References 44 publications
1
144
0
3
Order By: Relevance
“…Çalışmada ağrı ve nörotoksisite değerlendirilmiş olup, çalışmanın sonucuna göre her iki grupta da anlamlı bir fark bulunmadığı bildirilmiştir. (25) Farklı bir çalışmada ise hastaların 4 gruba ayrılarak sırasıyla elektroakupunktur, hidroelektrik bantlar, vitamin B1/B6, plasebo kapsülün etkinliği değerlendirildiğinde hiçbir yöntemin bir diğerine göre üstünlüğü kanıtlanamamıştır. (26) Multiple miyelom hastalarında thalidomide/bortezomib tedavisine bağlı gelişen nöropatinin yönetiminde elektroakupunkturun etkisinin değerlendirildiği non-randomize çalışmada ise 19 hasta değerlendirilmiştir.…”
Section: Elektroakupunkturunclassified
“…Çalışmada ağrı ve nörotoksisite değerlendirilmiş olup, çalışmanın sonucuna göre her iki grupta da anlamlı bir fark bulunmadığı bildirilmiştir. (25) Farklı bir çalışmada ise hastaların 4 gruba ayrılarak sırasıyla elektroakupunktur, hidroelektrik bantlar, vitamin B1/B6, plasebo kapsülün etkinliği değerlendirildiğinde hiçbir yöntemin bir diğerine göre üstünlüğü kanıtlanamamıştır. (26) Multiple miyelom hastalarında thalidomide/bortezomib tedavisine bağlı gelişen nöropatinin yönetiminde elektroakupunkturun etkisinin değerlendirildiği non-randomize çalışmada ise 19 hasta değerlendirilmiştir.…”
Section: Elektroakupunkturunclassified
“…Systematic reviews of the CIPN found that the effectiveness of current treatments (including natural products and complementary therapies) are still unknown and only vitamin E is shown to possibly help alleviate CIPN [7,8]. The current studies of acupuncture in CIPN vary in the use of different cancer and anti-cancer drugs such as taxanes for breast cancer [9], bortezomib and thalidomide for multiple myeloma [10], and a mix of neurotoxic anticancer drugs [11]. However, studies of acupuncture for oxaliplatin-induced peripheral neuropathy are rare and there has been no randomized controlled trial [12].…”
Section: Introductionmentioning
confidence: 99%
“…Different acupuncture techniques, for example, auricular acupuncture, have been shown to decrease pain intensity, while more standard reference points for needle insertion have also demonstrated neuropathic symptom improvement in cancer patients. 9 , 11 - 16 Reviews of integrative oncology services at our institution found that approximately one third of the patients receiving acupuncture are treated for peripheral neuropathy, 17 suggesting the need for continued research of its effectiveness.…”
Section: Introductionmentioning
confidence: 99%